Police In-Between Apoliticality and Politicality - Bäcker, Roman (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2022)
The paper aims to construct a theoretical tool that allows for possible precise location of relations between the police and the ruling elite in a given country. Their relationship is between the ideal types of apoliticality and politicality. The five stages of the relationship between the ruling elite and the bureaucracy on a continuum between the ideal type of the apolitical Weberian bureaucracy and its antinomic ideal type of politicised system of patronage can be arranged as follows: self-regulation, personal independence, uncertainty, loyalty, and enhanced loyalty. The empirical usefulness test of these stages scheme consisting in the case study of one state characterised by a large range of autocratic and democratic regimes evolution (thus post-war Poland) was positive. Relations between the police, or more precisely: the Citizens’ Militia, in the period of the Polish People’s Republic can be defined as being at the stage of enhanced, double loyalty. In the period of the Third Polish Republic, relations between the police and the ruling elites can be placed at the fourth stage – loyalty. The few attempts to change this type of relationship and move to the stage of self-regulation or personal independence remained at the level of ineffective and temporary attempts at best.

Celem tekstu jest skonstruowanie narzędzia teoretycznego pozwalającego na tak precyzyjne, jak tylko to możliwe usytuowanie relacji w danym państwie pomiędzy policją a elitą rządzącą. Relacje pomiędzy policją a elitą rządzącą mieszczą się pomiędzy typem idealnym apolityczności a typem idealnym polityczności. Pięć etapów relacji elit rządzących z biurokracją na continuum pomiędzy typem idealnym apolitycznej Weberowskiej biurokracji a antynomicznym mu typem idealnym upolitycznionym systemem patronażu można uszeregować następująco: samoregulacji, niezależności personalnej, niepewności, lojalności i wzmocnionej lojalności. Test empirycznej przydatności schematu powyższych pięciu etapów polegający na analizie przypadku jednego państwa charakteryzującego się dużą rozpiętością ewolucji reżimów autokratycznego i demokratycznego (a więc powojennej Polski) wypadł pozytywnie. Relacje między policją, a dokładniej: Milicją Obywatelską, w okresie PRL-u można zdefiniować jako znajdujące się na etapie wzmocnionej, bardziej precyzyjnie: podwójnej, lojalności. W okresie III RP relacje pomiędzy policją a elitami rządzącymi można usytuować na etapie czwartym – lojalności. Nieliczne próby zmiany tego typu relacji i przejścia na etap samoregulacji lub niezależności personalnej pozostawały na poziomie w najlepszym przypadku nieskutecznych i tymczasowych prób.
Policja pomiędzy apolitycznością a politycznością
Keywords: apoliticality of the police; politicality of the police; Weber’s theory of bureaucracy; patronage system; theoretical tool; apolityczność policji; polityczność policji; weberowska teoria biurokracji; system patronażu; narzędzie teoretyczne